Histological evaluation of the intestine of broiler chickens: comparison of three sampling methods - Marielen de Souza; Claudineia Emidio Cicero; Maísa Fabiana Menck-Costa; Larissa Justino; Juliana Rubira Gerez; Ana Angelita Sampaio Baptista; Ana Paula Frederico Rodrigues Loureiro Bracarense (Semina: Ciências Agrárias, 2021)
After the growth-promoting antibiotics prohibition, intestinal health became an increasing concern worldwide in poultry farming. The intestinal histological evaluation is an inexpensive technique that brings relevant information, but in poultry, the immediate process of intestinal post-mortem autolysis interferes directly on the samples quality for histological analysis hindering a precise diagnosis. This study aimed to standardize a technique for broilers’ intestines sample collection and fixation for histological analysis. Seven broiler chickens received a standard diet until 23 days of age when they were euthanized. Fragments of duodenum, jejunum, and ileum were collected using three methods: intestine strips, transverse section, and Swiss roll and posteriorly fixed in 10% buffered formalin and bouin solution. Tissue samples were submitted for histological (number of villi and viable villi per field) and morphometrical (villi height, crypt depth and villi:crypt ratio) evaluations and the results analyzed statistically. A significant high number of villi and viable villi per field in all regions was observed in the Swiss roll method. In the duodenum (p= 0.0066) and jejunum (p= 0.0058) an interaction between the Swiss roll method and the fixative buffered formalin was observed in the viable and number of villi per field, respectively. Regarding the morphometrical analysis significant differences were observed, in the jejunum villi height sampling by the methods Swiss roll (1,157.66 ± 148.25 µm, p= 0.0015) that showed the highest mean. Deeper crypt depths were observed in the jejunum (156.59 ± 15.68 µm, p= 0.0002) and ileum (131.13 ± 15.01 µm, p= 0.0006) collect by the Swiss roll method. An interaction between the bouin fixative was also observed in the jejunum (p= 0.0223) for this variable. Duodenum sampling by transversal section (12.68 ± 1.45 µm, p= 0.0076) was the only segment that had a significant difference for villi:crypt ratio, showing the highest mean. It can be concluded that the Swiss roll technique was the best method for morphometrical evaluation of the chickens’ intestines, since the highest counts of villi per field and viable villi per field were obtained, while buffered formalin was considered as the best fixative.